Geomorphology and community structure of Middle Reef, central Great Barrier Reef, Australia: an inner-shelf turbid zone reef subject to episodic mortality events - Browne, Nicola; Smithers, S.; Perry, C. (Springer Verlag, 2010)
Middle Reef is an inshore turbid zone reef located 4 km offshore from Townsville, Queensland, Australia. The reef consists of four current-aligned, interconnected reef patches that have reached sea level and formed reef flats. It is regularly exposed to high turbidity (up to 50 mg l-1) generated by wave-driven sediment resuspension or by episodic flood plumes. Middle Reef has a high mean hard coral cover (>39%), relatively low mean macro-algal cover (<15%) and a coral community comprising at least 81 hard coral species. Cluster analysis differentiated six benthic communities which were mapped onto the geomorphological structure of the reef to reveal a spatially patchy community mosaic that reflects hydrodynamic and sediment redistribution processes. Coral cover data collected annually from windward slope transects since 1993 show that coral cover has increased over the last ~15 years despite a history of episodic mortality events. Although episodic mortality may be interpreted as an indication of marginality, over decadal timescales, Middle Reef has recovered rapidly following mortality events and is clearly a resilient coral reef.